A research on the effectiveness of maintenance management for toilet of mosque in Selangor / Muhammad Yaser Yaacob - Yaacob, Muhammad Yaser (2009)
Malaysia already known with landmark in buildings with beautiful tall building and mosques. Mosque is one of unique building in Malaysia. Building dome structure and tower of mosque enough to show the characteristic and Islamic identity. Mosque role as muslims community place, administrative centre and knowledge spread and zakat collection center show the mosques as a multi functional institutional. Nevertheless, less of attention on mosque maintenance aspect are particularly at toilet part, now has made Islamic features and sanctity be in mosque building oozed away. A study on maintenance management was implemented through gathering of information and data from observation and questionnaire. Objective of the study would be To determine the characteristics of toilet clean in mosque, identify methods of maintenance work in toilet applied and to understand problems those occurring on toilet cause lack of maintenance management. Questionnaire form had been distributed to in the vicinity mosques Selangor. Result of analysis found that there is two method of maintenance namely by contract and cooperation. Apart from that also found two (2) problems that occurred at toilet which are dirty toilet and smelling and the second was incomplete and damaged facility problem. For decision of toilet clean characteristic user satisfaction and frequency clean the toilet. Respondent levels of satisfaction on toilet maintenance mosque mostly including maintenance work quality was less of satisfactory and make the maintenance management system's is less effectiveness of mosque toilet but it still relevance function with current situation.